THE NEEDS OF CONTINUING EDUCATION FOR ACADEMIC LIBRARIANS IN THE SOUTH OF THAILAND - Saechan, Chumchit (Malaysian Journal of Library and Information Science, 2005)
This study investigates the needs of continuing education for academic librarians in the south of Thailand and it compares those needs from the perspectives of two groups of people: academic librarians and library directors. The needs of continuing education focus on the technological topics preferences and the study proposes fifty-two topics of continuing education in eight technological categories. The results show that both groups perceive the Internet and Library Automation category as the most strongly recommended topics to be provided in the continuing education of academic librarians. The study also identifies the delivery and incentives preferences that would motivate librarians to engage in continuing education